SUMBANGAN ETIS MODEL BISNIS EKONOMI SIRKULAR TERHADAP PEMBANGUNAN YANG BERKELANJUTAN: EKSPLORASI KUALITATIF SISTEMATIK - Dionius Bismoko Mahamboro; Kristia Kristia (Jurnal Ledalero, 2021)
This study investigated the relationship between the circular economy amid the Covid-19 pandemic and Christian ethics using the latest literature in management, business ethics, and Christian ethics. Recently, many studies have been conducted on the circular economy, which is seen to be an alternate form of economic activity that benefits the underprivileged and the natural environment. However, it appears that the ethical implications of this circular economy have gotten limited attention. Christian ethics, especially the Catholic Social Teachings, provides a source of inspiration for the sustainable development of economic thought. The data analysis method used in this study was bibliometric analytical procedures, which involved collecting articles from Scopus, Google Scholar, and CrossRef databases. VOSviewer software was used to map keywords from these papers in order to identify research gaps in the region to be investigated. In addition, a qualitative analysis of the selected papers using the Atlas.ti program version 9 highlights the quantitative findings and delves deeper into the research themes. This research indicated that discussions about the circular economy are still mostly unrelated to aspects of ethics, morality, and religiosity, implying that more research is needed to go deeper into those areas.Key words: Catholic Social Teaching, bibliometric, circular economy, Christian ethics, Covid-19.